2018
DOI: 10.1371/journal.pone.0191469
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-induced benign prostatic hyperplasia rat and dog as facile models to assess drugs targeting lower urinary tract symptoms

Abstract: Benign prostatic hyperplasia (BPH) is an age-related disease, affecting a majority of elderly men worldwide. Medical management of BPH is an alternative to surgical treatment of this disease. Currently, α1-adrenergic receptor (α1-AR) antagonists are among the first line drugs to treat BPH by reducing the tension of urinary track and thus the obstructive symptoms in voiding. In drug development, old male dogs with spontaneous BPH are considered the golden standard of the animal models. However, old dogs (>6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
6
24
0
Order By: Relevance
“…Since Kato et al (1965) has reported pathologic growth of prostate tissue in TP-treated rats, this experimental model has been widely used by researchers for BPH research ( Maggi et al, 1989 ; Shin et al, 2012 ; Li et al, 2018 ). Based on this TP-induced BPH rat model, we attempted to elucidate the effect of BBR.…”
Section: Discussionmentioning
confidence: 99%
“…Since Kato et al (1965) has reported pathologic growth of prostate tissue in TP-treated rats, this experimental model has been widely used by researchers for BPH research ( Maggi et al, 1989 ; Shin et al, 2012 ; Li et al, 2018 ). Based on this TP-induced BPH rat model, we attempted to elucidate the effect of BBR.…”
Section: Discussionmentioning
confidence: 99%
“…These results further support the notion that supra-physiologic testosterone increases voiding frequency and are consistent with increased voiding frequency in rats and dogs supplemented with testosterone. 40…”
Section: Resultsmentioning
confidence: 99%
“…The testosterone-induced rat with BPH was used to explore the study about the development of obstruction in micturition and evaluation of drugs targeting the BPH problems [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%